(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article provides information about the importance of studying international experience in assessing the quality of education, a comprehensive comparative analysis of the existing system, close cooperation with international and foreign organizations, agencies, research institutes in the relevant field, the implementation of international projects to assess the quality of education, improving the appropriate national assessment system that meets the requirements of the time, etc.